The cognitive realism of memory in Flaubert's Madame Bovary - Troscianko, E (Modern Humanities Research Association, 2012)
The ‘cognitive realism' of memory in Madame Bovary is investigated by means of relevant research in the cognitive sciences, drawing conclusions which complement those of traditional literary criticism. In particular, Emma Bovary's memory is elucidated with reference to cognitive-dissonance theory: the human need for coherence between memory and self-image renders the trajectory of her married life psychologically explicable. The findings help account for critics' ambivalent or contradictory responses to Emma's story, and yield hypotheses concerning readers' responses more generally. They also suggest conclusions regarding the disjuncture between literary Realism (which corresponds to our assumptions about cognition) and cognitive realism (which corresponds to the underlying cognitive realities).